Applicability of the Richardson method in a complex-energy basis: Fermionic case - Civitarese, Enrique Osvaldo (2017)
We are testing the applicability of the algebraic procedure developed by Richardson for bound states to solve the pairing-force problem in presence of states with complex energies. This scenario, in which nucleons occupy single-particle states with complex energies and interact via the pairing force, is closely related to the microscopic description of nuclei with a large neutron (or proton) excess in basis which includes single-particle resonances. It is shown that the method gives results which are in good agreement with exact solutions. This finding is in coincidence with previously published works, by other authors, based on different methods to describe resonances.